TINJAUAN HUKUM EKONOMI SYARIAH DAN HUKUM POSITIF TERHADAP SKEMA PEMBEBANAN PAJAK DALAM TRANSAKSI QRIS (Quick Response Code Indonesian Standard) - Dhinar Adira Rachim; Mirza Yusuf Chandra, N; Muhammad Nurkamila Wardana; Jaenudin Jaenudin; Dian Herdiana (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study empirically examines the tax imposition scheme in QRIS transactions through normative legal analysis from two perspectives: Islamic economic law and Indonesian positive law. The study uses a qualitative method by analyzing legal documents, fatwas, and regulations. From a sharia perspective, QRIS is analyzed as a wakalah bil ujrah and ijarah contract in line with the principle of mashlahah mursalah. However, tax impositions such as MDR (Merchant Discount Rate) and VAT raise issues. These issues include double taxation, gharar, and injustice towards MSMEs, which contradict the maqashid sharia. This study proposes solutions through fair policy reform, education programs, DSN-MUI fatwas, and the implementation of blockchain technology. In positive law, QRIS is regulated by the HPP Law and PMK 69/2022. Tax objects include income tax on MDR and merchant income, as well as VAT on payment system services. This system involves various parties, including merchants and service providers. The main challenges identified are administrative complexity and limited understanding among MSMEs. This can be overcome through system integration such as the Coretax Administration System. The study concludes that QRIS can effectively support Indonesia's digital economy if taxes are levied transparently and fairly. Key recommendations include strengthening regulatory synergy to improve tax compliance and sustainable economic growth.